Primary ovarian carcinoid and dotanoc positron emission tomography-computed tomography scan - Gupta, Nitin; Dougall, Pankaj; Mahawar, Shruti (World Journal of Nuclear Medicine, 2019)
Primary ovarian carcinoids are very rare tumors, representing only <1% of all carcinoid tumors and <0.1% of all ovarian neoplasm. Here, we present a case report where DOTANOC positron emission tomography-computed tomography scan helped in diagnosis and management of rare entity.
Keywords: DOTANOC positron emission tomography-computed tomography scan; FDG positron emisson tomography; ovarian carcinoid